A STUDY ON THE EFFECTS OF LSL BRANDS ON CUSTOMERS - Krishna Karthikeyan, K.R. Shabu (International Journal of Advanced Science and Technology, 2020)
Nowadays in our country a new company is arriving in each day. In order to withstand in thiscompetitive world companies are maintaining a good corporate image in their customers mind.Branding, brand positioning, advertisements are the main tools. Branding helps the company topersuade the customers towards them. A study was made to know the effects of branding among thecustomers and to analyze their satisfaction towards the company. A sample of 100 customers wastaken for this study and interview method was used to collect information. Analysis was shown intables and pie charts and bar graphs.